Dealloying fabrication of hierarchical porous Nickel–Iron foams for efficient oxygen evolution reaction - Zhou, Tingting; Liu, Zilong; Yang, Bei; Cao, Zhen; Jiang, Zaiyong; Cui, Weiran; Wang, Kaili; Yu, Lei; Lu, Jitao; Zhang, Ling (Frontiers in Chemistry, 2022)
Designing and preparing highly active oxygen evolution reaction (OER) electrodes are essential for improving the overall efficiency of water splitting. Increasing the number of active sites is the simplest way to enhance OER performance. Herein, we present a dealloy-etched Ni–Fe foam with a hierarchical nanoporous structure as integrated electrodes with excellent performance for OER. Using the dealloying method on the Ni–Fe foam framework, a nanoporous structure is produced, which is named nanoporous Ni–Fe@Ni–Fe foam (NP-NF@NFF). Because of the peculiarities of the dealloying method, the NP-NF@NFF produced contains oxygen vacancies and heterojunctions. As a result, NP-NF@NFF electrode outperforms state-of-the-art noble metal catalysts with an extremely low overpotential of 210 and 285 mV at current densities of 10 and 100 mA cm−2, respectively. Additionally, the NP-NF@NFF electrode shows a 60-h stability period. Therefore, NP-NF@NFF provides new insights into the investigation of high-performance transition metal foam electrodes with effective active sites for efficient oxygen evolution at high current densities.